The relationship between prospective middle school mathematics teachers’ critical thinking skills and reflective thinking skills - Erdoğan, Fatma (Ozgen Korkmaz, 2020)
The aim of this study was to analyze the relationship between critical thinking skills and reflective thinking skills of prospective middle school mathematics teachers. In addition, it was aimed to examine critical thinking skills and reflective thinking skills of prospective middle school mathematics teachers with regard to some variables (gender, grade level, academic achievement level). This study adopts one of the general survey models: relational survey model. 201 prospective middle school mathematics teachers studying in Elementary Mathematics Teacher Education Program at a state university participated in this study. Reflective Thinking Scale and Critical Thinking Standards Scale were used. For the data analysis, descriptive statistics, independent sample t-test, one-way analysis of variance, correlation analysis, and simple linear regression analysis were used. The findings of this study showed that the prospective teachers' critical thinking skill level is high (agree), reflective thinking skill level is at moderate level (neutral). Critical thinking skills of the prospective teachers were significantly different in terms of gender and academic achievement. On the other hand, reflective thinking skills of the prospective teachers were significantly different in terms of grade level. Besides, there was a positive, significant and moderate relationship between critical thinking skills and reflective thinking skills of the prospective teachers. The prospective teachers’ critical thinking skills were the significant predictors of their reflective thinking skills. It was found that critical thinking skills explained 24% of the variance related to reflective thinking skills. © 2020, Ozgen Korkmaz. All rights reserved.
Keywords: Critical thinking; Mathematics education; Prospective mathematics teacher; Reflective thinking; Teacher education